PENGARUH MEDIA EDUKASI APLIKASI ANDROID BERBASIS WEBSITE TERHADAP PENGETAHUAN PENTINGNYA AKTIVITAS FISIK DALAM MENCEGAH DIABETES MELITUS PADA REMAJA (Studi di SMPN 12 Cimahi) - Arovah, Alif Zihadan; Ruhmawati, Tati (Politeknik Kesehatan Kemenkes Bandung, 2024)
The prevalence of diabetes mellitus cases has increased, with 7,604cases in 2019 rising to 10,640 cases in 2020 (Cimahi City Health Office, 2022). Basedon 2018 Riskesdas data from West Java Province, the proportion of physicalactivityamong residents aged ≥10 years was 62.51% sufficient and 37.49% less active. The 10-15 years age group also showed a low level of physical activity, witha proportion of68.14%. In Cimahi City, the proportion of physical activity amongresidents aged ≥10years was 44.65% sufficient and 55.35% less active (Riskesdas,2018b). Todetermine the effect of the Android Application-based Website educational media on theimportance of physical activity in preventing diabetes mellitus among adolescents atSMPN 12 Cimahi. Method: This research used mixed methods with a sequentialexploratory approach. Qualitative researchinvolved interviews for media needs with the4D media development model. Quantitative research used a quasi-experimentaldesign, a one-group pretest-posttest design, and probability sampling with a simplerandom sampling technique, involving 66 students. Data analysis was performed usingthe Wilcoxontest. Results: There was an increase in the average knowledge of studentsbefore and after being given the Android Application-based Website media, from 58.59to 83.45. The p-value for students' knowledge before and after being given the media,using the Wilcoxon test, was (p=0.000). Conclusion: There was a significant increasein knowledge and a significant influence after being provided with the AndroidApplication-based Website educational media on the knowledge of the importance ofphysical activity in preventing diabetes mellitus among adolescents at SMPN 12 Cimahi.